Effect of Pipe Material and Size on Water Losses at Different Networks in Egypt - , Vivian A. Khater; , Hanan A. Fouad; , Ahmed M. Abu El Magd; , Ahmed M. Hassanain (Archives of Current Research International, 2016)
Aims: This study was done in an attempt to reduce the percentage of losses in water treatment plants and networks by reducing its possible causes. Study Design: There are many causes for losses in water treatment plants and networks like water lost in water treatment plants due to washing filters and reservoirs, and water lost in networks due to the lack of maintenance or failure to renew ageing systems, illegal connection, metering errors, or accounting errors. Methodology: Data were collected for Damietta governorate, Egypt. The data collected include types of water treatment plants, capacity, water sold, losses for each water treatment plants and for networks losses, materials and diameters of pipes. Results: The interrelationships between types of water treatment plants, capacity, Quantity of water sold, losses, materials and diameters of pipes were studied, graphically represented, analyzed, and discussed in order to recommend the proper ways for reducing the losses. Conclusion: The study concluded that the developed compact water treatment plants is more preferred than surface water treatment plants as it reduced the percentage of losses by 2.5% compared to that of surface water treatment plants. The percentage of losses decrease with increasing the percentage of PVC, Cast-iron and GRP pipe lengths to the total lengths of all pipes. The percentage of losses increase with increasing the percentage of asbestos and steel pipe lengths to the total lengths of all pipes.